The influence school management and professional teachers motivation to the teachers in high school - Yuslah, Yustin; Lian, Bukman; Eddy, Syaiful (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This research to know the politically charged raid aimed at school management and motivation of teachers professional high school teacher in kecamatan pedamaran.hipotesis asked in this research , management is the professional senior high school teachers in schools to pedamaran sub district , work is the motivation to performance in kecamatan pedamaran high school teacher , is the school management and motivation, working together on the same high school teacher in kecamatan pedamaran professional .In penilitian , hifotesis in use is the partial ) ( t , the simultaneous ) ( f , a correlation coefficient ( r ) ( r2 ) and coefficients determined. The results of the analysis supported survey data the results of the analysis and interview prove that there is influence professional school management to senior high school teachers in kecamatan pedamaran, influence motivation is work on performance senior high school teachers in kecamatan pedamaran, influence school management and motivation is work together to same professional senior high school teachers in kecamatan pedamaran with significant standard α < 0,05.